COMPUTATION OF TWO-COMPONENT TRANSITION RATES OFPREEQUILIBRIUM STATES - Selman, A.; Jasim, M.; Shafik, Sh. (Iraqi Journal of Science, 2024)
Different transition rates of the nuclear preequilibrium states in the exciton modelwere numerically calculated in the present work, as well as the state density and matrixelement of the nuclear interaction. The calculations were based on the two-componentversion of the exciton model. Some comparisons were made with earlier calculations,and the results showed a good agreement. The results were explained on the bases of theeffects of the differences in the particle and hole numbers, as well as the type of theincident particle and its energy. The conclusions indicated that preequilibrium nuclearreactions induced by protons differ only by small fraction from those induced byneurons at low exciton states. At higher exciton states with n>3, the transitions of thetypes−nl and+pl differed significantly between neutron and proton transitions, whichmay indicate distinguishable nuclear reaction mechanisms.